The globalization of legal education : a critical perspective - Garth, Bryant G.; Shaffer, Gregory C., 1958- (New York, NY : Oxford University Press, 2022)
'The Globalization of Legal Education', with contributors from nine countries, seeks to critically understand the processes of legal education reform and resistance and to point to what these processes mean for law and lawyers inside and outside of the United States.
Also issued in print: 2022.
"This is an open access publication, available online and distributed under the terms of a Creative Commons Attribution - Non Commercial - No Derivatives 4.0 International licence (CC BY-NC-ND 4.0)"--Title page verso.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on May 26, 2022).
Keywords: Law -- Study and teaching; Law and globalization; Law; Jurisprudence & general issues